2022
DOI: 10.12998/wjcc.v10.i19.6520
|View full text |Cite
|
Sign up to set email alerts
|

Acute choroidal involvement in lupus nephritis: A case report and review of literature

Abstract: BACKGROUND Systemic lupus erythematosus (SLE), characterized by the production of autoantibodies and widespread deposition of immune complexes, predominantly affects women of childbearing age. More than one-third of SLE patients present ocular manifestations. Choroidal disease is currently not completely understood, and its precise differentiation from central serous chorioretinopathy is rarely achieved. To date, no more than 60 patients with choroidal involvement have been reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Lupus choroidopathy is a rare ocular manifestation of SLE that has been reported in no more than 60 patients up to 2019. [ 14 ] It is observed in patients with severe active or hypertensive SLE; therefore, it is considered an indicator of SLE activity. [ 4 ] Lupus choroidopathy is also associated with lupus nephritis because of the similar structure and pathogenesis of both the kidney and choroid.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lupus choroidopathy is a rare ocular manifestation of SLE that has been reported in no more than 60 patients up to 2019. [ 14 ] It is observed in patients with severe active or hypertensive SLE; therefore, it is considered an indicator of SLE activity. [ 4 ] Lupus choroidopathy is also associated with lupus nephritis because of the similar structure and pathogenesis of both the kidney and choroid.…”
Section: Discussionmentioning
confidence: 99%
“…reported that lupus nephritis was the most prominent comorbidity of lupus choroidopathy, occurring in approximately 78.6% of all patients. [ 14 ] In lupus nephritis, systemic hypertension is usually observed and exacerbates lupus choroidopathy because it contributes to choroidal vessel occlusion, which promotes choroidal ischemia and destruction of the blood–retinal barrier at the RPE. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations